LIVE STREAMING TIKTOK BAGI PENGUNJUNG WISATA PEMANDIAN LUBUK NAPA DALAM MENINGKATKAN PROMOSI PARIWISATA DI NAGARI SALIBUTAN, KECAMATAN LUBUK ALUNG - Lasmi, Ami; Efi, Agusti (Universitas Pendidikan Ganesha, 2025)
This study aims to examine the contribution of TikTok live streaming by visitors in increasing the popularity and attractiveness of Lubuk Napa Baths tourism in Nagari Salibutan. This type of research is qualitative by collecting data through observation, in-depth interviews, and documentation from visitors, tourism managers, and the surrounding community. Data were analyzed using thematic analysis methods to find digital promotion patterns that emerge naturally from visitors. The research findings indicate that TikTok live streaming significantly helps attract new tourists, especially from the younger generation. Content generated by visitors is considered more authentic and convincing than official promotions from managers.